A Road Map for Applying Relational Sociology - Kasapoglu, Aytul (Advances in Social Sciences Research Journal, 2019)
Abstract Relational sociology is based on the French and the German who first came to mind. It is important to note that Bourdieu and Elias are an introduction to relational sociology, although in the last 30 years different opinions or voices have been heard from America and Europe. For this purpose, following the process-based sociology of Bourdieu and Elias, Kivinen and Piiroinen (2013) were given to emphasize epistemology rather than ontology and to make it clear from metaphysical consideration. On the other hand, the work of White and his colleagues (2013) was handled in detail to represent relational sociological studies in the United States. As a result, the theoretical foundations of relational sociology under the metaphorical titles of three from Europe and one from America were tried to be explained in detail. In the conclusion part, relational sociology was made clear with some tables. Key words: Relational sociology, epistemology, Turkey.